PERANCANGAN BUKU KOMIK “SANGEDA & GAJAH PUTIH” - Iqbal Baihaqi, Dini Faisal, S.Ds., M.Ds., Hendra Afriwan, S.Sn., M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
The comic book "Sangeda & Gajah Putih" tells how the story about the appearance of the White Elephant in Aceh to The local comic fans as its primary target. The design goal was an effort to preserve one of Aceh's local cultural values in the form of printed media, namely comic books. The design method used in designing was a combination of the Glass-box and Black-Box methods. This design used a book titled "Gadjah Putih Iskandar Muda" written by a historian about White Elephant in Aceh in full and The interviews with three speakers as the main data source, and The additional data sources were obtained through observation, location documentation, and data on The Internet. Problem solving and data analysis are answered using a 5W + 1H data analysis model. The data is then used as a reference for drafting verbal and visual elements approaches of comic book “Sangeda & Gajah Putih”. The Drawing process of "Sangeda & White Elephant" Comic Book was completely done digitally using Drawing tablets. The final product of the design consists of the main media in the form of comic book as printed media and The supporting medias consisting of animations, posters, stickers, X-banners, papercraft, art books, T-shirts, Instagram accounts, and Webcomic..Keywords: White Elephant, Comic book, Folklore, Valueable local cultures of Aceh